ڕەهەندی کلتوریی بەجیهانیبوون - محمد, مامۆستاى یاریدەدەر. داڕێژ وریا (Sulaimani Journal for Humanities, 2023)
Globalization is an ancient and historical process and there are different opinions about history and its use as a concept in scientific and cognitive centers, and as a phenomenon and process has its own characteristics and distinctive features. It also has its own principles and objectives. On the other hand, in terms of support, globalization is divided into several directions (pro, anti and neutral), in the light of which its positive and negative effects are determined and presented. Both issues of globalization and culture are two interrelated issues, since globalization, which is to condense the world into a universal village, reduce the cost of time and distances, facilitate and accelerate communication, not only economic, political and social dimensions, but also One of the most important dimensions of globalization is the cultural dimension. Cultural globalization is the formulation and development of a particular culture at the global level. This process creates a wave of cultural similarities and affects all cultural characteristics. This process is related to cultural interaction and cultural change in societies, since cultural change is one of the distinctive characteristics of culture and no culture remains stationary, but in a state of relative stability and relative change. Cultural globalization also directly and indirectly, positively and negatively affects the culture and identity of different cultures of different societies in the world, including the culture of Kurdish society /Sulaimani is not excluded from these effects The components of its culture (material and spiritual elements) and ultimately on cultural and national identity.
Keywords: Keywords: globalization; culture; cultural change; cultural identity